The Quest for Stereoscopic Movement: Was the First Film ever in 3-D? (International Journal on Stereo & Immersive Media, 2017)
THE QUEST FOR STEREOSCOPIC MOVEMENT: WAS THE FIRST FILM EVER IN 3-D?   DENIS PELLERIN - London Stereoscopic Company